THE INITIAL RESULTS OF STUDYING THE SUSPENDED SEDIMENT DYNAMICS DURING THE FLOOD SEASON IN THE HAU RIVER MOUTH AREA - Tien, Nguyen Ngoc; Thanh, Nguyen Trung; Dang, Vu Hai; Vinh, Vu Duy (Vietnam Journal of Marine Science and Technology, 2016)
Land-ocean interactions in the coastal zone are severely influenced by tidal processces. In regions of high sediment discharge like the coast of Hau river estuary, these processes are even more significant when we analyse data in flood season (September) - which belongs to Agreement of Cooperation in Science and Technology between Vietnam and US (2013-2015) and project VAST-DLT.06/15-16 (2015-2016). Our goal is to investigate the sedimentation processes. Additionally, we investigated the influence of the tidal currents in relation to the suspended sediment. Salinity (PSU - Practical salinity unit), suspended sediment concentration (NTU - Nephelometric Turbidity Units) were measured by Compac-CTD (Depth temperature conductivity chlorophyll turbidity) and OBS-3A (Turbidity and Temperature Monitoring System) instruments. The results show that the suspended sediment concentration (SSC) correlate with tidal current velocities. The tidal current velocities are up to 60 cm/s near the surface and 40 cm/s near the bottom, increasing SSC in the water column at bottom layer (24 NTU) and decreasing SSC at surface layer (8 NTU). Processes of sediment transport and deposition in flood tide in flood season are influenced by tidal currents more significantly than those in dry season. This leads to an asymmetry of the tidal ellipses and the different deposition between seasons. The analytical results imply the influence of tide and tidal currents on SSC in the coast of Hau river estuary, hence, the spread, sea water and fresh water mixing processes have difference during tidal phases and seasons.